2007
DOI: 10.1038/sj.ijo.0803570
|View full text |Cite
|
Sign up to set email alerts
|

A reciprocal interaction between food-motivated behavior and diet-induced obesity

Abstract: Objectives: One of the main causes of obesity is overconsumption of diets high in fat and sugar. We studied the metabolic changes and food-motivated behavior when rats were subjected to a choice diet with chow, lard and a 30% sucrose solution (high fat high sugar (HFHS)-choice diet). Because rats showed considerable variations in the feeding response to HFHS-choice diet and in food-motivated behavior, we investigated whether the motivation to obtain a sucrose reward correlated with the development of obesity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
128
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 36 publications
(71 reference statements)
14
128
1
Order By: Relevance
“…Previous studies have examined FSA in both Ob Zucker and diet-induced obese (DIO) rats under an FR schedule and experimental procedures similar to ours (Glass et al, 1999;la Fleur et al, 2007). In these studies, operant lever responses for food did not differ between obese and lean animals (Glass et al, 1999;la Fleur et al, 2007). Nevertheless, operant responding behavior in obese rats seems to be subject to the specific schedule of reinforcement.…”
Section: Zucker Ob Rats and Fsamentioning
confidence: 95%
“…Previous studies have examined FSA in both Ob Zucker and diet-induced obese (DIO) rats under an FR schedule and experimental procedures similar to ours (Glass et al, 1999;la Fleur et al, 2007). In these studies, operant lever responses for food did not differ between obese and lean animals (Glass et al, 1999;la Fleur et al, 2007). Nevertheless, operant responding behavior in obese rats seems to be subject to the specific schedule of reinforcement.…”
Section: Zucker Ob Rats and Fsamentioning
confidence: 95%
“…The procedure used for operant conditioning was adapted from (la Fleur et al, 2007, Tracy et al, 2008b. All rats were subjected to a mild food restriction paradigm during which their initial body weight was gradually reduced to 90% over a period of one week.…”
Section: Trainingmentioning
confidence: 99%
“…14 Moreover, rats on the HFHS diet showed alterations in the level of the hypothalamus. We observed that within the arcuate nucleus of the hypothalamus, the expression of neuropeptide Y increased and that of proopiomelanocortin decreased when rats were fed a free-choice HFHS diet.…”
Section: Introductionmentioning
confidence: 99%